2017
DOI: 10.1038/npp.2017.149
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of Impaired BKCa Channel Function in Sensory Defensiveness and Some Behavioral Disturbances Induced by Unfamiliar Environment in a Mouse Model of Fragile X Syndrome

Abstract: In fragile X syndrome (FXS), sensory hypersensitivity and impaired habituation is thought to result in attention overload and various behavioral abnormalities in reaction to the excessive and remanent salience of environment features that would normally be ignored. This phenomenon, termed sensory defensiveness, has been proposed as the potential cause of hyperactivity, hyperarousal, and negative reactions to changes in routine that are often deleterious for FXS patients. However, the lack of tools for manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…Early in life, FXS patients present auditory, olfactory, nociceptive and visual abnormalities (Casamassimo et al, 1986 ; Lachiewicz et al, 1994 ), creating a wide range of phenotypical dysregulations in sensory responses. These sensorial perturbations may participate in occurrence of major behavioral troubles in FXS as suggested recently (Carreno-Munoz et al, 2018 ). According to our hypothesis, the term “sensorial hypersensitivity”, literally suggesting a higher sensorial response, should be avoided.…”
Section: Discussionmentioning
confidence: 68%
“…Early in life, FXS patients present auditory, olfactory, nociceptive and visual abnormalities (Casamassimo et al, 1986 ; Lachiewicz et al, 1994 ), creating a wide range of phenotypical dysregulations in sensory responses. These sensorial perturbations may participate in occurrence of major behavioral troubles in FXS as suggested recently (Carreno-Munoz et al, 2018 ). According to our hypothesis, the term “sensorial hypersensitivity”, literally suggesting a higher sensorial response, should be avoided.…”
Section: Discussionmentioning
confidence: 68%
“…The present study found that Fmr1 -KO rats showed enhanced locomotor activity for the first 30 min after placement in a novel environment but not at 30–60 min or 60–90 min. Studies using Fmr1 KO mice have reported that the hyperactivity was a reaction to novelty 42 , 43 . Our results from Fmr1 -KO rats suggest that the hyperactivity may be a reaction to novelty, because the significant augmentation in locomotor activity was only observed for the first 30 min after placement in a novel testing field.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, direct injection of the activator restored hippocampal glutamate homeostasis and corrected disturbances in social recognition and interaction, non-social anxiety and spatial memory ( Hebert et al, 2014 ). In another study, BMS-204352 efficiently reversed the cortical hyperexcitability and increased acoustic startle seen in FMR1 knockout mice ( Carreno-Munoz et al, 2018 ), suggesting that this treatment could alleviate sensory hypersensitivity symptoms in FXS patients.…”
Section: Regulation Of K Ca Channels and Implicatimentioning
confidence: 97%